Multidisciplinary approach and anesthetic management of a surgical cancer patient with methylene tetrahydrofolate reductase deficiency: a case report and review of the literature. (December 2015) - Cascella, Marco; Arcamone, Manuela; Morelli, Emanuela; Viscardi, Daniela; Russo, Viera; De Franciscis, Silvia; Belli, Andrea; Accardo, Rosanna; Caliendo, Domenico; De Luca, Elena; Di Caprio, Barbara; Di Sauro, Francesco; et al.
Abstract Introduction Hyperhomocysteinemia is a known risk factor for myocardial infarction, stroke, peripheral vascular disease, and thrombosis. Elevated plasma homocysteine levels have been demonstrated in patients with recurrent episodes or a single episode of thrombosis. Here we describe the development of cardiovascular disease as a complication of a surgical intervention in a patient with colorectal cancer and hyperhomocysteinemia. Case presentation A 65-year-old Caucasian man complained of pain and constipation, attributed to previously diagnosed adenocarcinoma (stage IIB) of the hepatic flexure. An anamnestic investigation showed that he had undergone two surgical interventions. During both, he suffered thrombotic postoperative complications, a deep vein thrombosis of the upper extremity after the first operation and retinal vein occlusion after the second. He was diagnosed with hyperhomocysteinemia associated with a homozygous C677T mutation of the gene encoding the enzyme methylenetetrahydrofolate reductase. Our patient was initially treated with folic acid and high-dose B vitamins. On day 7 he underwent a right hemicolectomy. Anesthesia was performed with sevoflurane in 40% O2 and without the use of nitrous oxide. Postoperatively, our patient remained on folic acid and B vitamins and was without immediate or subsequent complications. Conclusions Neoplastic disease and related surgery followed by the administration of chemotherapeutic drugs alter the hemostatic balance in cancer patients. Those suspected of also having a thrombophilic disease require a thorough laboratory diagnostic workup, including a molecular analysis aimed at identifying the genetic mutation responsible for the hyperhomocysteinemia, as indicated. The case described in this report highlights the importance of a multidisciplinary approach that includes expertise in peri-operative anesthesia, surgery, oncology, and hematology.